The technology of medications. General issues of medicines manufacturing. Production of water solutions and galenicals : Manual to practical classes for pharmaceutical students 4-d year study specialty 226 “Pharmacy” - Burlaka, B. S.; Gladyshev, V. V.; Nagorniy, V. V.; Puchkan, L. O.; Gladysheva, S. A.; Бурлака, Богдан Сергійович; Гладишев, Віталій Валентинович; Нагорний, Володимир Володимирович; Пучкан, Любов Олександрівна; Гладишева, Світлана Анатоліївна (Запорізький державний медико-фармацевтичний університет, 2024)
Based on the requirements of the Technology of Medications Work Program, this book presents the main theoretical issues and provides practical tasks for compounding of medicines – galenical, extracts, syrups and etc. The book contributes to the students comprehension and visualization of Pharmaceutical Compounding and is designed in a clear scheme. Заснований на вимогах робочої програми з технології ліків, цей посібник представляє основні теоретичні питання та практичні завдання стосовно промислового виготовлення сиропів, настоянок, особливостей екстракції. Складений за прозорою схемою, посібник сприяє розумінню та уявленню студентами промислового виготовлення ліків.